Rural non-farm income of small farm producers in Colombia - Polo-Murcia, Sonia Mercedes (2021)
This study analysed the composition of rural non-farm income (RNFI) of small agricultural producers in four regions of Colombia. We used the Colombian Longitudinal Survey (ELCA) for 2010, 2013 and 2016. The RNFI represents, on average, 38 % of total household income, with variations between 30 % for the largest production units and 50 % for the smallest. The participation of non-agricultural rural income within the total household income is higher and statistically significant in female-headed households, most of which are devoted to self-employment activities. These results have implications for both the formulation of public policies and for the management of agricultural production at the household level in Colombia